Specific features of consumer's behaviour in new market economies - Iryna Lylyk (International Economic Policy, 2008)
Despite intuitive or deliberate realization of the necessity of being oriented towards the customer’ s needs, the marketing philosophy was not used similarly in real life by the enterprises of the new market-oriented countries, among which we traditionally find the Baltic countries (Latvia, Lithuania, Estonia), Poland, Czech Republic, Hungary, Romania, Bulgaria, Ukraine, Russia, the former Ugoslavian republics (Slovenia, Croatia, Serbia, Chernogoria) and others. The article generalizes the factors, influencing the behavioral peculiarities of the consumers in the above-mentioned countries and specific ways of introduction of marketing technologies and it is supported by the reprinted materials or by the results of the comparative research, carried out by research institutions and professional associations.